Upper tract access in patients with urinary diversions - Modai, Jonathan; Bhanji, Yasin; Patel, Parth M.; Scotland, Kymora; Dunn, Matthew D. (Frontiers in Urology, 2024)
Urinary tract diversions are a common reconstructive solution for patients with malignant, anatomic or functional pathologies of the lower urinary tract. Although urinary diversions often represent the patient’s best alternative, they are not devoid of complications. Some of these complications, mainly anastomotic strictures and kidney stones, can be managed endoscopically, although upper tract access of such patients is not straightforward, requiring a fundamental understanding of the many types of diversions. In this article we will review the inherent difficulties of accessing the upper tract of patient with different diversions, the different approaches to the upper tract of diverted patients, and the equipment and techniques that can help facilitate upper tract access in diverted patients.